PSYCHOLOGICAL WELLBEING PERAWAT IGD RUMAH SAKIT JIWA DALAM MASA TUGAS COVID-19: STUDI FENOMENOLOGI - Febriana Tri Kusumawati; Luky Dwiantoro; Devi Nurmalia (LPPM STIKES Muhammadiyah Kendal, 2021)
The COVID-19 pandemic experienced by people around the world has resulted in an increase in the number of patients and stressors for nurses in Mental Hospital Emergency Departments, and is exacerbated by the condition of mental patients who are unable to communicate properly. The quality of patient care in the ER is determined by the availability of the 5M element where nurses as a human element in the COVID-19 pandemic situation require more attention regarding psychological wellbeing. Psychological wellbeing of good nurses will have a positive impact on nursing services in the ER mental hospital. The purpose of this study was to explore the experiences and feelings of psychologic wellbeing of Surakarta mental hospital emergency room nurses during the COVID-19 period. The research method used a qualitative design on the emergency room nurse mental hospital used Colaizzi analysis method. The results of the analysis of the participant interviews obtained seven themes, namely the meaning of psychological wellbeing (feeling happy, grateful to accept one's own condition, comfortable, useful and productive), Feelings during the COVID-19 pandemic (feelings at the beginning of the pandemic and current feelings), How to adapt during the COVID-19 pandemic. -19 (increased self-readiness, mutual care and support for fellow nurses, fulfillment of facilities and improvement of service systems), Hope for the COVID-19 pandemic (Joking freely and the pandemic will end soon and no health workers will fall), Changes experienced during the COVID-19 pandemic 19 (changes in regulations and culture in the face of a pandemic, changes in methods of studying online), experiences during work (pleasant experiences and bad experiences), families who always support carers (spouses and children and parents), and the impact of the COVID-19 pandemic ( towards others and towards family). The conclusion now is that nurses feel more comfortable and calm in carrying out their duties. The nurses had made adaptations to reduce anxiety so as to improve the psychological wellbeing status of the nurses.